2016
DOI: 10.1123/jsr.2015-0118
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Joint Positions for Manual Isometric Muscle Testing

Abstract: Context Manual isometric muscle testing is a common clinical technique that is used to assess muscle strength. To provide the most accurate data for the test, the muscle being assessed should be at a length in which it produces maximum force. However there is tremendous variability in the recommended positions and joint angles used to conduct these tests, with little apparent objective data used to position the joint such that muscle force production is greatest. Objective To use validated anatomically and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Indeed, the joint angles used closely resemble those used in other isometric strength assessment studies that were not designed to compare torque during different contraction types, including for hip flexion and extension [ 44 ], hip adduction and abduction [ 36 ], and knee flexion and extension [ 30 , 33 , 37 ]. By individually optimizing the joint angle to the point where the torque was highest, we maximized the torque-length relationship of the muscle by theoretically locating the point with the most filament overlap [ 18 , 19 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the joint angles used closely resemble those used in other isometric strength assessment studies that were not designed to compare torque during different contraction types, including for hip flexion and extension [ 44 ], hip adduction and abduction [ 36 ], and knee flexion and extension [ 30 , 33 , 37 ]. By individually optimizing the joint angle to the point where the torque was highest, we maximized the torque-length relationship of the muscle by theoretically locating the point with the most filament overlap [ 18 , 19 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to methodological constraints since the magnitude of peak joint torques is only reasonable to compare when the optimal joint torque angle is applied during isometric contractions [ 11 , 23 ]. Although some recommendations for an optimal joint angle for maximum torque are available [ 33 37 ], deviations through individuals anthropometry exist, and therefore optimal joint angles unique to each individual should be obtained beforehand in order to produce a true maximal isometric torque measurement [ 15 ]. However, this has not been included in previous studies comparing torque differences between contraction types.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum isometric knee extensor strength is peaked around 60 o of knee flexion. 2,15 This study is concerned more about the positioning to allow the recording of absolute maximum force output in the isometric knee extensor muscles while still preventing the subjects to overpower the examiner and also preventing difficulties in stabilizing equipment on subjects' legs. The previous studies stated that one of the problems found in isometric knee extensor muscle strength measurement is that the examiners were not able to give proper pressure against subjects' maximum force while stabilizing the equipment on the legs.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements of muscle strength appropriate for application in clinical practices can be performed using a manual muscle testing (MMT) and hand-held dynamometer (HHD) . [1][2][3] Manual muscle testing is commonly used in clinical settings for screening muscle strength; however, it is subjective and less sensitive. On the other hand, HHD is able to give objective results and also more sensitive than the MMT; therefore, it is more suitable to be used for diagnosing weakness in quadriceps femoris muscle and for the post-treatment evaluation of the muscle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation